PENGARUH TINGKAT UPAH, STRES KERJA, DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS SOPIR TRUK PADA PT SEMESTA TRANSPORTASI LIMBAH INDONESIA - Anisa Sifi Begedina Depari; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2016)
Productivity’s driver is very important to be considered in order to achieve the goals of the company. Productivity can be influenced by several factors, including wage , job stress, and work motivation. Semesta Transportasi Limbah Indonesia,ltd is a company engaged in sector of land transport services which decreased productivity driver over in 2013-2015. The purpose of this research is to find influence wage, job stress, and work motivation on the productivity of a truck driver in the Semesta Transportasi Limbah Indonesia,ltd.. The research uses a quantitative approach. A population is 76 driver using saturation sampling. Data collection using the questionnaire. The analysis in this research using SPSS version 17.0.The results showed that the wage does not affect the productivity with the t value 1.309 < t table 1.9925. Job stress influence productivity with t score 3.490. Work motivation influence productivity with 2,967 t. however simultaneously wage levels, job stress and work motivation affects productivity with F count 7.421 > F table 2,73 with the significance 0.000 <0.005. Suggestions for companies to improve his attention on wage is considered less good, and to job stress and work motivation have several indicators that are less optimal that ultimately can increase work productivity’s truckers.